THE INTERACTIONS OF MADZHABS IN ACEH: The Tripolar Typology - Fauzi Fauzi (State Islamic University North Sumatra, 2017)
Abstract: Interaksi Madzhab di Aceh: Sebuah Tipologi Tripolar. Penelitian ini bertujuan untuk melihat model interaksi di antara berbagai mainstream mazhab yang berkembang dalam praktik masyarakat Aceh. Penulis menemukan bahwa terdapat tiga tipologi interaksi mazhab di Aceh, pertama; eksklufisme yang meyakini bahwa mazhab Syâfi’i merupakan model fikih yang layak untuk diikuti sebagai akibat pengajaran fikih selama ini berorientasi pada satu mazhab berkembang pada milieu pendidikan informal seperti Dayah. Kedua, inklusivisme, dimana masyarakat cenderung bermazhab Shâfi‘î baik dalam ‘ibâdah maupun mu‘âmalah, sekalipun tetap membuka ruang bagi mazhab lain untuk diikuti. Ketiga, pluralisme yang beranggapan bahwa mazhab hanya merupakan sarana untuk memahami agama. Penulis menyimpulkan bahwa masyarakat perkotaan cenderung pada dua tipologi terakhir dalam bermazhab yang dikembangkan oleh pendidikan formal seperti perguruan tinggi Islam. Untuk membangun Aceh modern, masyarakat harus memahami mazhab secara tepat dan memposisikannya sebagai salah satu model pemahaman shari’ah yang menjadi rahmat li al-‘âlamîn sebagai social engineering. Abstract: This study aims to analyze the model of interactions amongst various legal school of thoughts in contemporary Aceh. This study was a field study with the qualitative method. The method used to analyze the data was descriptive analysis. In this research, it is revealed that the dynamic of interactions of Islam in spins around three typologies which are exclusivism, inclusivism and pluralism. As for the first typology, it is believed that the Shâfi‘î madhab is the only legitimate school and thus should be abide by. The second polar is inclusivism, a typology in which society tends to adhere to Shâfi‘î madhab in the realm of religious observation (‘ibâdah) and (mu‘âmalah) though it still gives room and tolerate any other madhabs to to survive side by side. The author asserts that this typology could be considered the neutral way to solve the current religious problems in Aceh. The third polar is pluralism that can be utilized as a principal standard in building the harmony, peace and respect amongst the Acehnese in order to accomplish the ultimate goal of Islam as rahmat li al-‘âlamîn. Keywords: Islamic law, madhab, Aceh, exclusivism, inclusivism, pluralism